Wardair plane -- photograph ... - Seale, Linda N. (University of Alberta Library, 2012)
Plane on display at Old Airport Road, Yellowknife : the first Bristol Freighter in the North : used by Wardair, an airline based in Yellowknife and Edmonton, founded in 1953 by bush pilot Max Ward, initially using small bush planes. This aircraft was used to bring in the town fire truck, farm animals, and general freight, in particular when the Mackenzie River crossing was closed during fall freeze-up and spring break-up of ice. It could carry 45 drums of fuel and had a long enough range to fly to the Beaufort Sea during drilling activity there. Wardair became a holiday charter airline and was sold to Canadian Airlines in 1989. Photograph taken March 2012 ...